The Influence of Occupational Safety and Health (K3) on the Performance of Avsec Officers at Sultan Muhammad Salahuddin Bima Airport - Ilmiatun, Nurul; Nieamah, Kartika Fajar (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Every work carried out at the airport has its own potential dangers. Likewise with the risk of danger experienced by Avsec personnel, considering that there have been many cases that threaten the security and safety of Avsec personnel on duty. Muhammad Salahuddin Bima needs to implement an Occupational Safety and Health (K3) program that can protect physical and mental safety and health in order to improve the performance of Aviation Security officers. Quantitative methods were used in this research, which focused on all Aviation Security (AVSEC) officers on duty at Sultan Muhammad Salahuddin Airport located in Bima. A total of 40 respondents were selected as samples for this research. Primary and secondary data sources were used to collect relevant information, while validity, reliability, linear regression analysis, t-test and coefficient calculation were applied for data analysis. Based on the t-test carried out in this research, variable X has a positive and significant effect on Y. The t-test result for In addition, it was found from this research that only 0.67% of the contribution in influencing the performance of Avsec officers only came from considering occupational safety health variables while other factors/external independent variables were responsible for the remaining 99.33%.